1999
DOI: 10.1292/jvms.61.891
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical Analysis of Sex and Strain Differences in the Mouse Nephron.

Abstract: ABSTRACT. In the present study, we investigated the sexual dimorphisms, effects of castration and sex hormone treatment, and strain differences in the morphology of mouse kidney by measuring the percentage of renal corpuscles with cuboidal cells in the parietal layer of the glomerular capsule, the diameter of renal corpuscles and the number of nuclei of epithelial cells in the proximal convoluted tubule. In ICR mice, the percentage of renal corpuscles with cuboidal cells and the diameter of renal corpuscles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 11 publications
1
32
2
Order By: Relevance
“…Moreover, changes in diameter of renal corpuscles may have been affected not only by changes in glomerular size, but also by changes in height of the parietal layer of glomerular capsules. Actually, the presence of a cuboidal parietal layer in the glomerular capsules represents a well-known morphological feature of the adult male mouse kidney, and the relationship between the diameter of renal corpuscles and the height of the parietal layer of glomerular capsules has already been suggested [18]. The present study failed to demonstrate any association between increased renal corpuscle diameter and glomerular damage in the course of age-dependent nephropathy.…”
contrasting
confidence: 71%
“…Moreover, changes in diameter of renal corpuscles may have been affected not only by changes in glomerular size, but also by changes in height of the parietal layer of glomerular capsules. Actually, the presence of a cuboidal parietal layer in the glomerular capsules represents a well-known morphological feature of the adult male mouse kidney, and the relationship between the diameter of renal corpuscles and the height of the parietal layer of glomerular capsules has already been suggested [18]. The present study failed to demonstrate any association between increased renal corpuscle diameter and glomerular damage in the course of age-dependent nephropathy.…”
contrasting
confidence: 71%
“…The parietal layer of the glomerular capsule commonly consists of squamous cells. However, in the laboratory mouse, morphological features of this layer differ among the sexes, with males exhibiting cuboidal cells [15,17,29]. Except for mice, sex-based morphological differences in the parietal layer of the glomerular capsule had not been evaluated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric analysis: Randomized morphometric analysis was performed according to previous methods by using PAS-stained sections (5 sections/animal): 1) diameter of the cortical renal corpuscles which were located in the superficial and middle areas of cortex [29], 2) diameter of the juxtamedullary renal corpuscles which were located in the juxtamedullary area of cortex [29], 3) percentage of the renal corpuscles with a cuboidal parietal layer (CPL) [29], 4) number of nuclei in proximal convoluted tubules (PCTs) per unit area of cortex (100,000 µm 2 ) [29], 5) semi-quantitative score of the PAS-positive granules in PCTs, and 6) semi-quantitative score of the PAS-positive granules in proximal straight tubules (PSTs). Semi-quantitative analysis of the PAS positive granules were performed as follows.…”
Section: Animalsmentioning
confidence: 99%
“…In our recent studies, we have demonstrated strain and sex-based morphological varieties of mouse kidneys [6,7]. In these studies, we investigated kidney morphology in male and female mice from five strains (ICR, BALB/c, C3H/He, C57BL/6, and DBA/2), and identified femalespecific cytoplasmic granules in the proximal straight tubules (PSTs) [7].…”
mentioning
confidence: 99%